THE EFFECT OF MEDIUM INTENSITY PHYSICAL ACTIVITY ON BLOOD GLUCOSE LEVELS IN DIABETES MELLITUS - R.A. Tanzila; Ni Made Elva Mayasari; Dita Azzahra Maso (International Islamic Medicine Forum, 2020)
Diabetes mellitus (DM) is a chronic disease that increased every year and caused many complications. There are four pillars in the management of DM, namely education, nutrition, pharmacology and physical training. According to PERKENI, physical exercise for people with DM can be done 3-4x/week with a duration of 30 minutes. This study aims to determine the effect of exercise moderate activities carried out by Diabetes Mellitus in Muhammadiyah Hospital Palembang on blood sugar levels at a time. This study uses a quasi-experimental method with a total sample of 30 people who were obtained by total sampling. The research data was taken by checking blood sugar before and after physical activity with aerobic type, which is done 1x/week for four weeks by using Easy Touch GCU. Wilcoxon test results found a p-value of 0.285 which means moderate exercise activities carried out by people with diabetes in Palembang Muhammadiyah Hospital which is carried out once a week for four weeks does not affect blood sugar levels at the time.